Corrigendum to "The readability 'Sangkuriang': asal-mula tangkuban perahu' folklore for elementary school students using gunning fog index" - Welsi Damayanti; Jendriadi; Ida Nuraeni; Abdul Razak (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This corrigendum addresses an error in the originally published version of this article. An author's name was incorrectly spelled in the author byline and the running header. The name was published as 'Welsi Damyanti' when it should have appeared as 'Welsi Damayanti'. The authors sincerely apologize for this oversight and any inconvenience it may have caused. The online version of the article has been amended to reflect this correction.